Stirring time effect of silver nanoparticles prepared in glutathione mediated by green methods - Balavandy, Sepideh Keshan; Shameli, Kamyar; Awang Biak, Dayang Radiah; Zainal Abidin, Zurina (Chemistry Central, 2014)
Background: This study aims to investigate the influence of different stirring time for synthesis of silver nanoparticles in glutathione (GSH) aqueous solution. The silver nanoparticles (Ag-NPs) were prepared by green synthesis method using GSH as reducing agent and stabilizer, under moderate temperature at different stirring times. Silver nitrate (AgNO3) was taken as the metal precursor while Ag-NPs were prepared in the over reaction time. Results: Formation of Ag-NPs was determined by UV–vis spectroscopy where surface plasmon absorption maxima can be observed at 344–354 nm from the UV–vis spectrum. The synthesized nanoparticles were also characterized by X-ray diffraction (XRD). The peaks in the XRD pattern confirmed that the Ag-NPs possessed a face-centered cubic and peaks of contaminated crystalline phases were unable to be located. Transmission electron microscopy (TEM) revealed that Ag-NPs synthesized were in spherical shape. Zeta potential results indicate that the stability of the Ag-NPs is increases at the 72 h stirring time of reaction comparison to GSH. The Fourier transform infrared (FT-IR) spectrum suggested the complexation present between GSH and Ag-NPs. The use of green chemistry reagents, such as peptide, provides green and economic features to this work. Conclusions: Ag-NPs were successfully synthesized in GSH aqueous solution under moderate temperature at different stirring times. The study clearly showed that the Ag-NPs synthesized in the long times of stirring, thus, the kinetic of GSH reaction is very slow. TEM results shows that with the increase of stirring times the mean particle size of Ag-NPs become increases. The FT-IR spectrum suggested the complexation present between GSH and Ag-NPs. These suggest that Ag-NPs can be employed as an effective bacteria inhibitor and can be applied in medical field.